The Role Of The Administrative Justice System In Public Administration - Shokirova Dilnoza Bakhodir kizi (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article presents an analysis of the importance of the administrative justice system in the current state administration system and its features. In addition, the views of legal scholars on the administrative justice system and methods for protecting citizens' rights and restoring their violated rights are also covered.